Citarum River Water Pollution and Stress Responses in The Tolerant and Sensitive Fish - Sunardi Sunardi; Kabul Fadilah; Nadia Istiqomah; Miranti Ariyani; Desak Made Malini; Syifa Yolanda; Azalea Putri; Nining Ratningsih (Indonesian Journal of Limnology, 2021)
Severe river pollution creates a stressful environment for aquatic organisms, causing disturbances to their health and leading to their extinction. Thus, in this study, the stress responses of tolerant (Oreochromis niloticus) and sensitive (Cyprinus carpio) fish to river pollution in the Citarum River, Indonesia were investigated. The two groups of fish were exposed to varying levels and lengths of water pollution, their blood was sampled, and stress responses were identified. The red blood cells (RBC) count, haemoglobin (HGB), haematocrit (HCT), white blood cells (WBC) count, blood glucose levels, and derived haematological indices such as mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC), were measured. Significant changes in these indices, with tendential changes in RBC and HCT, were observed, indicating that stress responses had occurred in both groups of fish. The sensitive fish recorded more pronounced changes in their haematological activities, with greater amounts of blood parameters being altered in response to water pollution exposure. This result suggested that the sensitive fish were more susceptible to environmental stressors and were, therefore, more vulnerable to extinction in a polluted natural environment.